Beyond dive shape: the identification of fine-scale vertical movements reveal within-dive behavioural structure in a pursuit-diving seabird - Astrid Dedieu; Mark Jessopp; Sam L. Cox (Marine Biology, 2026)
Understanding how diving predators exploit prey in dynamic marine environments provides insight into their foraging strategies, energetic trade-offs, and capacity to adapt to changing conditions. While traditional classifications of dive shape have provided valuable albeit coarse insights, fine-scale behaviours embedded within dives, such as prey encounter/capture attempts, can be overlooked. We used time-depth recorders (TDR) deployed on Atlantic puffins ( Fratercula arctica ) between 2021 and 2025 on Skellig Michael, County Kerry, Ireland (51.7707°N, 10.5405°W) to detect fine-scale vertical undulations (“wiggles”) in dives as proxies for prey-capture attempts. We used a broken-stick model to divide dives into segments and built a custom function to identify wiggles within segments. Wiggle occurrence differed significantly among dive phases ( p < 0.001). Wiggles were most frequent during the ascent and bottom phases. Less than 10% of wiggles occurred during descent phases, despite descent making up 30.3% of the time spent diving. Our findings indicate that puffins, like other pursuit-diving predators, forage not only during the bottom phase but extensively while surfacing. More broadly, the integration of broken-stick segmentation with wiggle detection provides a simple, transferable framework for quantifying prey-capture attempts across pursuit-diving predators. This approach enhances inference from TDR data and contributes to a comparative understanding of how diving predators partition foraging effort within dives.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The effect of seasonality on the foraging behaviour and breeding success of a tropical marine top predator - Sarah Saldanha; Teresa Militão; Sam L Cox; Irene Llamas-Cano; Herculano Andrade Dinis; Ivandra S.G.C. Gomes; Artur Lopes; Maldini dos Santos; Vania Brito; Marcos Hernández-Montero; Jacob González-Solís (Progress in Oceanography, 2025)

Protocol-in-a-Day Workshop: Expediting IRB Approval for Junior and Senior Faculty - Geina M. Iskander; Adriana Cavazos; Chinenye Lynette Ejezie; Victoria Cox; Hunter Cheng; Shelby Perez; Albert C. Koong; Jonathan Nguyen; Joseph Herman; Sam Beddar; Zhongxing Liao; Debra Nana Yeboa (Journal of Cancer Education, 2025)

Low pH enhances germination of eelgrass (Zostera marina L.) seeds despite ubiquitous presence of Phytophthora gemini - Alyson Lowell; Claudia E.L. Hill; Sam Dupont; Eduardo Infantes; Kirti Ramesh; Bradley Peterson; Laura L. Govers; T. Erin Cox (Aquatic Botany, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

How Does Ocean Acidification Affect the Early Life History of Zostera marina? A Series of Experiments Find Parental Carryover Can Benefit Viability or Germination - Alyson Lowell; Eduardo Infantes; Laura West; Lauren Puishys; Claudia E. L. Hill; Kirti Ramesh; Bradley Peterson; Just Cebrian; Sam Dupont; T. Erin Cox (Frontiers in Marine Science, 2021)
Elevated partial pressure of carbon dioxide ( p CO 2 ) as a concomitant of global climate change may facilitate the establishment of future seagrass meadows and subsequently its benefit could be incorporated into techniques to increase restoration success. In five manipulative experiments, we determined how increased CO 2 affects the maturation of flowers, and the development of seeds and seedlings for the foundation species Zostera marina . Experiments tested the development from both seeds collected from non-treated flowering shoots (direct) and seeds harvested from flowering shoots after CO 2 exposure (parental carryover). Flowering shoots were collected along the western coast of Sweden near the island of Skafto. The seeds produced were used in experiments conducted at Kristineberg, Sweden and Dauphin Island, AL, United States. Experiments varied in temperature (16, 18°C) and salinity (19, 33 ppt), as well as duration and magnitude of elevated CO 2 exposure. Flowering maturation, spathe number, seed production, and indicators of seed quality did not appear to be affected by 39–69 days of exposure to CO 2 conditions outside of natural variability ( p CO 2 = 1547.2 ± 267.60 μatm; pH T = 7.53 ± 0.07). Yet, seeds produced from these flowers showed twofold greater germination success. In another experiment, flowering shoots were exposed to an extreme CO 2 condition ( p CO 2 = 5950.7 ± 1,849.82 μatm; pH T = 6.96 ± 0.15). In this case, flowers generated seeds that demonstrated a fivefold increase in an indicator for seed viability (sinking velocity). In the latter experiment, however, germination appeared unaffected. Direct CO 2 effects on germination and seedling production were not observed. Our results provide evidence of a parental CO 2 effect that can benefit germination or seed viability, but early benefits may not lead to bed establishment if other environmental conditions are not well suited for seedling development. Outcomes have implications for restoration; CO 2 can be supplied to flowering shoot holding tanks to bolster success when the purpose is to redistribute seeds to locations where beds are extant and water quality is adequate.

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)